Tugas dan Wewenang Kepala Desa di Desa Oabikase dan Desa Kiusili di Tinjau dari Undang-Undang No 6 Tahun 2014 tentang Desa - Philipus Neri Ahoinnai; Saryono Yohanes; Yohanes G. Tuba. Helan (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
Village community empowerment is the duty and authority of the Village Head as contained in article 26 of Law Number 6 of 2014 concerning Villages, it is stated that the Village Head is in charge of organizing Village Government, implementing Village Development, Village Community Development and Village Community Empowerment. Village government organizational structure The village head is the leader of the village helpers/officials. This research was conducted in Oabikase Village, West Insana District, and Kiusili Village, South Bikomi District, TTU Regency. This research basically uses empirical juridical research methods, namely: research carried out directly to related parties in order to obtain information on the problem under study. Respondents are methods that take the pointer process based on the purpose for which information is to be obtained, then 44 people are used. According to the author's observations, the community in Oabikase Village and Kiusili Village are still not independent and prosperous in knowledge, ability and skills, so there are indications that the Village Head has not carried out his duties and authorities to optimally improve community empowerment. Although BUMDes have been established in the two villages, because the abilities, skills and knowledge of the community are still limited so they have not been able to use them optimally. The implementation of the duties of the village head in community empowerment and the use of Oabikase Village and Kiusili Village in Kefamenanu District, North Central Timor Regency has not run optimally, this is evident from the uneven infrastructure development. Oabikase Village and Kiusili Village still have factors that hinder government administration activities, including human resources.